ANALISIS IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH DASAR NEGERI 115 PEKANBARU - Zaka Hadikusuma Ramadan Mail (Universitas Negeri Medan, 2020)
This study aims to describe; 1) the implementation of character education values in terms of the planning and implementation process in SD Negeri 115 Pekanbaru; 2) behavior of SD Negeri 115 Pekanbaru students in applying the values of religious character, honesty, diligence, discipline, and care / responsibility. This study uses a quantitative descriptive approach with survey methods. The location of this research was carried out at the SD Negeri 115 Pekanbaru City, having its address at Jalan Handayani, Sidomulyo Timur Mapoyan Pekanbaru, Riau Province. Data collection techniques in this study are; 1) interview; 2) observation; 3) questionnaire (questionnaire); and 4) documentation. The results showed that the tendency of the implementation of character education values in the good category was 8 people (12.7%), while in the sufficient category there were 46 people (73.0%) and in the poor category 9 people (14.3%). So it can be concluded that the tendency of the implementation of the value of character education in SDN 115 Pekanbaru is in the sufficient category.Keywords: Character education, SDN 115 Pekanbaru